2017
DOI: 10.1007/s13361-017-1781-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Proteins, Protein Complexes, and Organellar Proteomes Using Sheathless Capillary Zone Electrophoresis - Native Mass Spectrometry

Abstract: Native mass spectrometry (MS) is a rapidly advancing field in the analysis of proteins, protein complexes, and macromolecular species of various types. The majority of native MS experiments reported to-date has been conducted using direct infusion of purified analytes into a mass spectrometer. In this study, capillary zone electrophoresis (CZE) was coupled online to Orbitrap mass spectrometers using a commercial sheathless interface to enable high-performance separation, identification and structural character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
110
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(113 citation statements)
references
References 88 publications
3
110
0
Order By: Relevance
“…Examples include size exclusion chromatography (SEC), ion exchange chromatography (IEC), hydrophobic interaction chromatography (HIC), and capillary electrophoresis (CE). 1619 On-line separations offer notable advantages to infusion-based native MS applications. MS spectra can be correlated with retention time (RT) to provide orthogonal confirmation of isoform assignments.…”
Section: Introductionmentioning
confidence: 99%
“…Examples include size exclusion chromatography (SEC), ion exchange chromatography (IEC), hydrophobic interaction chromatography (HIC), and capillary electrophoresis (CE). 1619 On-line separations offer notable advantages to infusion-based native MS applications. MS spectra can be correlated with retention time (RT) to provide orthogonal confirmation of isoform assignments.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, detection of aggregates is an important advantage of the analytical technique for characterization of mAbs. A previous study out of our lab has also reported on dimers detected in native CZE-MS analysis for a different mAb [2]. In addition to aggregates, species corresponding to dissociated light chain and light chain dimers, as well as intact mAb with a loss of two light chains were also observed.…”
Section: Figures 3-15 A-c Proteoform Identifications Limited To Glycmentioning
confidence: 63%
“…A trace quantity of the mAb is thereby composed of light chain domains bound via non-covalent interactions instead of disulfide bonds. The presence of such species has been reported previously, and such fragments are known to occur under native conditions [2,[286][287][288].…”
Section: Intact Cze-ms Characterization Of the Mabmentioning
confidence: 74%
See 2 more Smart Citations